Hearing Practices in the Yakthung (Limbu) Customary Judicial System - Subba, Kshitij (Indigenous Nationalities Studies आदिवासी जनजाति अध्ययन, 2025)
The Yakthung (Limbu) an indigenous nationality of Limbuwan have Mundhum as a philosophical source of authoritative jurisprudential guidance. So, the Yakthung customary law and judicial system are based on Mundhum jurisprudence. In the Yakthung customary judicial system, the hearing is an important part of the justice dispensation system; however, there is not sufficient knowledge about it. This article explores the facts and relevancy of the Chumlung, the hearing practices of the Yakthung, as it seems to be practicable and relevant for even the contemporary legal system. The Yakthung hearing practices were very egalitarian and consensus-oriented. The practice contained the concept of public hearing and group-based judgment system. Parties were free to present their demand and evidence. Various types of penalties existed but apology and forgiveness were the main factors to solve the dispute with amicable solutions. Apology and forgiveness were the main tools during hearings, convictional verdicts and penalization. That creates easiness and longevity of conflict resolution.